A robust multicriteria analysis for the post-treatment of digestate from low-tech digesters. Boosting the circular bioeconomy of small-scale farms in Colombia. (September 2022) - Juanpera, M.; Ferrer-Martí, L.; Diez-Montero, R.; Ferrer, I.; Castro, L.; Escalante, H.; Garfí, M.
Abstract: Low-tech digesters are sustainable technologies to produce a clean fuel (biogas), which can be used for cooking and heating. Moreover, the degradation of organic waste in the digester also produces a liquid effluent (digestate), which can be reused in agriculture as a biofertilizer. The direct application of digestate to the soil may not be either feasible due to regulations or safe due to poor quality. The study aims to apply, for the first time, a multicriteria analysis to select the most suitable solution for the post-treatment and reuse of digestate from low-tech digesters implemented in small-scale farms. The post-treatments considered are: a degassing tank, a sand filter, a vermifilter, digestate recirculation, a facultative pond, and combinations of them. Ten criteria and twenty-one sub-criteria including technical, environmental and socio-economic aspects are defined to be weighted by experts. The analysis employs triangular fuzzy numbers to consider uncertainty and increase the robustness of the results, and it is validated using three case studies in Colombia. The alternatives are designed using data collected in-situ on the design and operation of the digesters and the quality of the digestates. Results confirm the robustness of the rankings and show that vermifiltration is the best alternative for the post-treatment of digestates from low-tech digesters implemented in small-scale farms. It is due to the fact that it produces a high-quality biofertilizer, it is easy to manage and it is implemented using local materials. Other prominent alternatives are sand filtration, recirculation and a degassing tank coupled with vermifiltration. Highlights: Alternatives for post-treatment of digestate from low-tech digesters are assessed. 21 technical, environmental and socio-economic subcriteria are defined. The fuzzy multicriteria methodology MIMDU is used to obtain robust results. Alternatives are designed using data from three real small farms in Colombia. Vermifilter is the best option, with sand filters and digestate recirculation.